Human placenta‐derived adherent cells induce tolerogenic immune responses. Issue 5 (2nd May 2014) - Liu, Wei; Morschauser, Andrew; Zhang, Xin; Lu, Xiaohua; Gleason, Joseph; He, Shuyang; Chen, Hong‐Jung; Jankovic, Vladimir; Ye, Qian; Labazzo, Kristen; Herzberg, Uri; Albert, Vivian R; et al.
Abstract : Human placenta‐derived adherent cells (PDAC cells) are a culture expanded, undifferentiated mesenchymal‐like population derived from full‐term placental tissue, with immunomodulatory and anti‐inflammatory properties. PDA‐001 (cenplacel‐L), an intravenous formulation of PDAC cells, is in clinical development for the treatment of autoimmune and inflammatory diseases. To elucidate the mechanisms underlying the immunoregulatory properties of PDAC cells, we investigated their effects on immune cell populations, including T cells and dendritic cells (DC) in vitro and in vivo . PDAC cells suppressed T‐cell proliferation in an OT‐II T‐cell adoptive transfer model, reduced the severity of myelin oligodendrocyte glycoprotein peptide‐induced experimental autoimmune encephalomyelitis and ameliorated inflammation in a delayed type hypersensitivity response model. In vitro, PDAC cells suppressed T‐cell proliferation and inhibited Th1 and Th17 differentiation. Analysis of tissues derived from PDAC cell‐treated animals revealed diminished CD86 expression on splenic DC, suggesting that they can also modulate DC populations. Furthermore, PDAC cells modulate the differentiation and maturation of mouse bone marrow‐derived DC. Similarly, human DC differentiated from CD14 + monocytes in the presence of PDAC cells acquired a tolerogenic phenotype. These tolerogenic DC failed to induce allogeneic T‐cell proliferation and differentiation toward Th1, but skewed T‐cell differentiation toward Th2. Inhibition of cyclo‐oxygenase‐2 activity resulted in a significant, but not complete, abrogation of PDAC cells' effects on DC phenotype and function, implying a role for prostaglandin E2 in PDAC‐mediated immunomodulation. This study identifies modulation of DC differentiation toward immune tolerance as a key mechanism underlying the immunomodulatory activities of PDAC cells. Immunity: Seeking out secrets of placental protection: The same mechanisms that protect the fetus from the mother's immune system could help keep autoimmune and inflammatory diseases at bay. A growing body of evidence suggests that placental cells promote maternal tolerance for fetal tissues that might otherwise be perceived as 'foreign'. Bitao Liang and colleagues at Celgene Cellular Therapeutics in Warren, New Jersey, USA, examined the role of cultured human 'placenta‐derived adherent cells' (PDAC® cells), with a view toward developing these cells as therapeutic tools. Cell culture and animal model experiments both demonstrated that PDAC® cells can help restrict proliferation and activation of T‐cell subsets associated with certain immune disorders. The authors found that this occurs through direct effects on T cells and also through factors secreted by PDAC® cells. These factors promote development of particular immune cells that help limit the overall immune response.